PROSPECTIVE ANALYSIS OF ALGAL BIODIESEL PRODUCTION - Reis, Marcello; Marciano Martinez , Maria Elisa; Guimarães Vasconcellos , Alexandre (Journal of Mechatronics Engineering, 2021)
This article aims to carry out an initial patent mapping of algal biodiesel. The production of algal biodiesel is one of the forms of third generation biodiesel; it is an environmentally friendly alternative energy whose main advantage is that it does not compete with food, as the algal biodiesel is produced from synthesized lipids by algae in growth using sunlight. The methodology used was the patent mapping by activity having as search criteria: the Espacenet database (“worldwide”); and, the keyword: biodiesel and algae and algal biodiesel. It was observed that about 80% of the family of patent documents referring to this technology were applied between 2007 and 2016 and that these documents were published mainly in China (34% of patent documents), followed by the United States (25% of patent documents) and thirdly, the World Intellectual Property Organization (WO), that is, the PCT’s international patent application, which indicates an interest in protection in several countries (15% of patent documents). Concluding that China and the United States are the countries that invest the most in the development and protection of technologies related to the production of algal biodiesel, however, the interest in protection goes beyond these countries, since the interest in alternative energies is worldwide.